Peningkatan Keterampilan Menulis Deskriptif Bahasa Inggris Peserta Didik Kelas X IPA1 Melalui Pembelajaran Berbasis Proyek - Dwi Mulyani (INTELEKTIUM, 2020)
This research aims to improve writing skills through the project-based learning model. The research subjects were 36 students. Data collection methods used are observation, testing, and documentation. The act of learning the first cycle of students describe a tourism place. On the second cycle, they describe a tourism place. Cycle II is more focused on linguistic and non-linguistic aspects, which are still lacking. The evaluating system that was suitable for this research was planning, implementation, and project evaluation. Improvement is indicated by the results of students' writing skills scores. The increase occurred: (1) the average value of student pre-cycle by 72,75 rose to 78,06; (2) the first cycle was 78,06 with a percentage of completeness of 50%; (3) the second cycle is 84,46 with an 84,37 % completeness percentage.